HCV Proteins and Immunoglobulin Variable Gene (IgV) Subfamilies in HCV-Induced Type II Mixed Cryoglobulinemia: A Concurrent Pathogenetic Role - Giuseppe Sautto; Nicasio Mancini; Laura Solforosi; Roberta A. Diotti; Massimo Clementi; Roberto Burioni (Clinical and Developmental Immunology)
The association between hepatitis C virus (HCV) infection and type II mixed cryoglobulinemia (MCII) is well established, but the role played by distinct HCV proteins and by specific components of the anti-HCV humoral immune response remains to be clearly defined. It is widely accepted that HCV drives the expansion of few B-cell clones expressing a restricted pool of selected immunoglobulin variable (IgV) gene subfamilies frequently endowed with rheumatoid factor (RF) activity. Moreover, the same IgV subfamilies are frequently observed in HCV-transformed malignant B-cell clones occasionally complicating MCII. In this paper, we analyze both the humoral and viral counterparts at the basis of cryoglobulins production in HCV-induced MCII, with particular attention reserved to the single IgV subfamilies most frequently involved.